Teacher Education and Youngsters with Learning Problems, Par III: The Problem Pupil and the Specialist Teacher. - Adelman, Howard S. (Journal of Learning Disabilities, 1972)
In the preceding two articles in this series, the focus has been on exploring the general issues and problems related to improving the quality of teacher education programs. The question now arises as to what additional substantive issues and problems must be clarified with reference to personnel who are to have an impact on pupils with learning/behavior problems. However, before this question can be answered intelligently, it is necessary to clarify the nature and scope of the pupil population involved. Therefore, the first parts of this third and final installment are devoted to a brief summary of this writer's views regarding that pupil population, including a statement of some implications of these views for classroom practices; the remainder of the article explores additional issues and problems with reference to special education personnel.